Surface processing to improve the fatigue resistance of advanced bar steels for automotive applications - David K. Matlock; Khaled A. Alogab; Mark D. Richards; John G. Speer (Materials Research, 2005)
With the development of new steels and processing techniques, there have been corresponding advances in the fatigue performance of automotive components. These advances have led to increased component life and smaller power transfer systems. New processing approaches to enhance the fatigue performance of steels are reviewed with an emphasis on carburizing and deep rolling. Selected examples are presented to illustrate the importance of the base steel properties on the final performance of surface modified materials. Results on carburized gear steels illustrate the dependence of the fatigue behavior on carburizing process control (gas and vacuum carburizing), alloy additions and microstructure. The importance of retained austenite content, case and core grain size as controlled by processing and microalloy additions, extent of intergranular oxidation, and the residual stress profile on fatigue performance is also illustrated. Specific recent results on the use of microalloying elements (e.g. Nb) and process history control to limit austenite grain growth at the higher carburizing temperatures associated with vacuum carburizing are highlighted. For crankshaft applications, deep rolling is highlighted, a process to mechanically work fillet surfaces to improve fatigue resistance. The influence of the deformation behavior of the substrate, as characterized by standard tensile and compression tests, on the ability to create desired surface properties and residual stress profiles will be illustrated with data on several new steels of current and future interest for crankshaft applications.